Yield Responses of Grain Sorghum and Cowpea in Binary and Sole Cultures under No-Tillage Conditions in Limpopo Province - Tlou E. Mogale; Kingsley K. Ayisi; Lawrence Munjonji; Yehenew G. Kifle (Agriculture, 2022)
Climate change is severely disrupting ecosystem services and crop productivity, resulting in lower crop growth and yields. Studies have emphasized the importance of assessing conservation practices through crop modelling to improve cropland productivity. There is a lack of accurate information in the performance of conservation practices as well as data for improved crop modelling. No-tillage sorghum–cowpea intercrop experiments were established to assess the productivity of four sorghum cultivars and cowpea at two densities of 37,037 and 74,074 per plants and generate data for improved crop modelling. The leaf area index (LAI) varied in sorghum cultivars and cowpea densities during the two growing seasons. Cultivars Enforcer and NS5511 produced the highest grain yields of 4338 kg per ha and 2120 kg per ha, respectively, at Syferkuil. Ofcolaco’s Enforcer and Avenger were the highest yielding cultivars at Ofcolaco, with mean yields of 2625 kg per ha and 1191 kg per ha, respectively. At Syferkuil, cowpea yield was 93% and 77% more in sole compared to binary cultures during the growing seasons at Syferkuil. At Ofcolaco, sole yielded approximately 96% more grain than binary. The findings confirm that for the sorghum–cowpea intercrop to improve overall system productivity, cowpea density should be increased.